STRATEGI PENINGKATAN EKONOMI KREATIF DALAM MENUNJANG INDUSTRI PARIWISATA DI DESA DENIANG - SUSI WARDHANI, RULYANTI (KRIDA CENDEKIA, 2021)
Deniang Village has promising potential in the tourism sector because not only are the beaches very beautiful but the natural potentials it has are also very diverse which can be processed into a source of strengthening a creative-based economy. This research is a descriptive study with data collection through interviews and library methods. The purpose of this research is to provide a strategy in optimizing the potential of the village to become a means of creative economy in order to improve the tourism industry in Deniang Village. The results show that the strategy carried out in optimizing the creative industry in accordance with the potential of Deniang Village is by advancing the hydroponic program in Deniang Village as a means of creating the potential of the Hydroponic Tourism Village, the potential for the creation of coconut bonsai as a typical souvenir of coastal village crafts, and optimizing the potential utilization. The abundant fisheries in Deniang Village have become various products that are of sale value.